FIGNL1 Inhibits Non-homologous Chromosome Association and Crossover Formation - Yang, Shuying; Zhang, Chao; Cao, Yiwei; Du, Guijie; Tang, Ding; Li, Yafei; Shen, Yi; Yu, Hengxiu; Cheng, Zhukuan (Frontiers in Plant Science, 2022)
Meiotic crossovers (COs) not only generate genetic diversity but also ensure the accuracy of homologous chromosome segregation. Here, we identified FIGNL1 as a new inhibitor for extra crossover formation in rice. The fignl1 mutant displays abnormal interactions between non-homologous chromosomes at diakinesis, and chromosome bridges and fragmentation at subsequent stages of meiosis, but shows normal homologous chromosome pairing and synapsis during early prophase I. FIGNL1 participates in homologous chromosome recombination and functions downstream of DMC1. Mutation of FIGNL1 increases the number of bivalents in zip4 mutants, but does not change the number of HEI10 foci, indicating that FIGNL1 functions in limiting class II CO formation. FIGNL1 interacts with MEICA1, and colocalizes with MEICA1 in a dynamic pattern as punctate foci located between two linear homologous chromosomes. The localization of FIGNL1 depends on ZEP1-mediated assembly of the synaptonemal complex. Based on these results, we propose that FIGNL1 inhibits non-homologous chromosome interaction and CO formation during rice meiosis.